Here comes the flood! Stress effects of continuous and interval waterlogging periods during the growing season on Scots pine saplings. (18th March 2020) - Domisch, Timo; Qian, Ji; Sondej, Izabela; Martz, Françoise; Lehto, Tarja; Piirainen, Sirpa; Finér, Leena; Silvennoinen, Raimo; Repo, Tapani
Abstract: Future climate scenarios for the boreal zone project increasing temperatures and precipitation, as well as extreme weather events such as heavy rain during the growing season. This can result in more frequent short-term waterlogging (WL) leading to unfavorable conditions for tree roots. In addition, it is decisive whether short-term WL periods during the growing season occur continuously or periodically. We assessed the effects of short-termed WL on 4-year-old Scots pine ( Pinus sylvestris L.) saplings after shoot elongation started. Waterlogging (WL) lasted either continuously for 2.5 weeks (ContWL) or noncontinuously for 5 weeks, consisting of three repeated 1-week-interval WL periods (IntWL). Both treatments resulted in the same duration of soil anoxia. We studied soil gases, root and shoot growth and physiology, and root survival probability and longevity during the experiment. In the final harvest, we determined shoot and root biomass and hydraulic conductance and electrical impedance spectra of the root systems. Soil CO2 and CH4 concentrations increased immediately after WL onset and O2 decreased until anoxia. Waterlogging decreased fine root survival probability, but there was no difference between WL treatments. Shoot growth suffered more from ContWL and root growth more from IntWL. Needle concentrations of pinitol increased in the WL saplings, indicating stress. No WL effects were observed in photosynthesis and chlorophyll fluorescence. Increased starch concentration in needles by WL may be due to damaged roots and thus a missing belowground sink. Electrical impedance indicated suffering of WL saplings, although root hydraulic conductance did not differ between the treatments. Oxidative stress of short-term and interval WL can have long-lasting effects on shoot and root growth and the physiology of Scots pine. We conclude that even short-term WL during the growing season is a stress factor, which will probably increase in the future and can affect carbon allocation and dynamics in boreal forests.